Case Report: Diagnostic and Therapeutic Challenges in Severe Mechanobullous Epidermolysis Bullosa Acquisita - Schauer, Franziska; Nyström, Alexander; Kunz, Manfred; Hübner, Stefanie; Scholl, Sarah; Athanasiou, Ioannis; Alter, Svenja; Fischer, Judith; Has, Cristina; Kiritsi, Dimitra (Frontiers in Immunology, 2022)
Collagen VII is the main constituent of the anchoring fibrils, important adhesive structures that attach the epidermis to the dermal extracellular matrix. Two disorders are caused by dysfunction of collagen VII, both characterized by skin and mucosa fragility, epidermolysis bullosa acquisita (EBA) and dystrophic epidermolysis bullosa (DEB). EBA and DEB share high clinical similarities with significant difference in patients' age of onset and pathogenesis. Our patients presented with severe and recalcitrant mechanobullous EBA with characteristic DIF, IIF and ELISA diagnostics. But in both women recessive COL7A1 variants were also found, in a monoallelic state. Collagen VII from EBA keratinocytes of our cases was significantly more vulnerable to proteolytic degradation than control keratinocytes, hinting that the heterozygous pathogenic variants were sufficient to destabilize the molecule in vitro. Thus, even if the amount and functionality of mutant and normal type VII collagen polypeptides is sufficient to assure dermal-epidermal adhesion in healthy individuals, the functionally-impaired proteins are probably more prone to development of autoantibodies against them. Our work suggests that testing for COL7A1 genetic variants should be considered in patients with EBA, which either have a patient history hinting towards underlying dystrophic epidermolysis bullosa or pose therapeutic challenges.